Adsorption of CO2 on Amine-Grafted Activated Carbon - Bezerra, Diôgo P. (2014)
Adsorption on amine-grafted materials may be a potentially attractive alternative to capturing CO2 from power plants. Activated Carbon (AC) has been proposed as a potential adsorbent due to its natural affinity for CO2 and to the possibility of tailoring textural properties and surface chemistry to enhance capacity and selectivity. An AC commercial sample was functionalized with monoethanolamine (MEA) in order to obtain nitrogen-enriched AC with two different loadings (ACN10 and ACN20). Samples characterization was carried out by nitrogen adsorption/desorption isotherms at 77 K, XPS, FTIR and adsorption microcalorimetry. CO2 equilibrium adsorption experiments were accomplished in a volumetric system in the pressure range of vacuum up to 10 bar, at 298 and 348 K. Impregnated activated carbon presented different chemical and textural characteristics with a significant reduction in the surface area, depending on the amine loading. A high adsorption capacity at room temperature and high pressure was observed for the pristine AC as compared to the modified samples. The reduction in surface area affected the adsorption capacity of CO2 at 298 and 348 K, except for adsorption on ACN10 at 348 K, which suggests the occurrence of chemisorption.